A critique of irrational elements in African beliefs (2009)
Various researches show that irrational elements in human beliefs^ otherwise known as superstition, just as they were criticised in ancient Greek and Roman societies, have been challenged in Europe and America as well. This paper highlights how individuals and organizations in Africa have similarly raised their voices against the increasing controversial stories of claims of supernatural influences or interferences in human affairs, suppression of thoughts, sexual abuse and extra-judicial inflicting of punishment or killing by individuals professing authority from spiritual realm. After a brief consideration of the socio-religious atmosphere that engenders the romance with the supernatural sphere, this work shows how the prevalent recourse to mystery in providing reasons for extraordinary occurrences could be most subjective. It then relates how what may seem a private expression of socio-cultural or religious views is confronted with criticism when it infests the public domain with disquieting concerns. The paper illustrates how practices rooted in superstition are perceived as growing threats to people's welfare in the continent. When the subject is understood in these terms, more meaning could be added to the search for a solution to sporadic religious, political and social conflicts in Africa.